PENGELOLAAN PENGEMBANGAN DESTINASI PARIWISATA BERKELANJUTAN PADA OBJEK WISATA PANTAI CAROCOK PAINAN - Widya Silviana; Adil Mubarak (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2020)
Management of Sustainable Tourism Destination Development at Carocok Painan Beach Tourism Object. This research describes the management of sustainable tourism development on the coast of Carocok Painan. Sustainable tourism focuses on aspects of sustainable tourism, namely from an economic, social and cultural perspective. Which in that local communities must be involved in tourism activities, as well as fair share of the benefits that are obtained specifically in the creation of direct and indirect employment. This research qualitative methods. The selection of informants was carried out by using purposive sampling technique. The data validity test used triangulation technology. Collecting data through interviews and library research. Data analysis technology is carried out through data reduction, data representation, and data verification. The results showed that it could be said that the development of sustainable tourism on the coast of Carocok Painan was very smooth. Even in the development of sustainable tourism, there are still shortcomings and obstacles.